ANALISIS PERFORMA TURBIN ANGIN VAWT (VERTICAL AXIS WIND TURBINE) TIPE HYBRID SAVONIUS DARRIEUS NACA 4712 - Muhammad Trifiananto; Irvan Septianto Putra; Mochamad Edoward Ramadhan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2022)
A wind turbine is a device that converts wind energy into mechanical energy to produce electric power. Wind turbines have a simple working principle, which is to convert wind energy into mechanical energy in the windmill, then the rotation of the turbine0makes the rotor on the generator rotate and generate electricity. There are 2 types of wind turbines: vertical axis wind turbine and horizontal axis wind turbine. This study aims to determine the performance of the medium-scale VAWT hybrid savonius darrieus NACA 4712 wind turbine. The hybrid wind turbine is a combination of savonius and darrieus wind turbines to increase efficiency by utilizing the drag of the savonius turbine and lift force from the darrieus wind turbine. This study used an experimental method. The fan is used to vary the wind speed. The wind speed used ranges from 5, 5.5, 6, 6.5, 7, 7.1,7.2,7.3 m/s. This savonius darrieus hybrid wind turbine can produce efficiency of 0.037 at wind speed of 5 m/s with an initial torque of 0.088 N/m. The maximum rotation in this hybrid turbine study 118 Rpm was obtained at a wind speed of 7.3 m/s.